Diabetes Self-Management Education (DSME) for Enhancing Knowledge and Self-Care Behaviors in Type 2 Diabetes Mellitus Patients: A Systematic Review - Dewi, Nofrika; Armiyati, Yunie; Mubin, Mohammad Fakhul (Media Keperawatan Indonesia, 2025)
Various strategies have been implemented to improve knowledge and self-care management in patients with Type 2 Diabetes Mellitus (T2DM). Among these, Diabetes Self-Management Education (DSME) programs have demonstrated positive effects on patients’ knowledge and self-care behaviors. This systematic review aims to evaluate the impact of DSME on enhancing knowledge and self-care behaviours among patients with T2DM. The review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature searches were performed across multiple databases, including ScienceDirect, ProQuest, PubMed, and Google Scholar. Inclusion criteria comprised articles published between 2020 and 2024, written in English or Indonesian, and published in reputable national or international journals. The search keywords used were “DSME” AND “knowledge” AND “self-care behavior.” Ten articles meeting the inclusion criteria were reviewed. The findings indicate that DSME significantly improves patients’ understanding of diabetes and promotes positive changes in self-care behaviors, suggesting its effectiveness as a critical component in diabetes management. This systematic review supports the integration of DSME programs into nursing practice to enhance outcomes for patients with T2DM.